Body-related concerns and participation in physical education among adolescent students: the mediating role of motivation - Haug, Ellen; Castillo, Isabel; Samdal, Oddrun; Smith, Otto Robert Frans (Frontiers in Psychology, 2023)
Background There is a need to understand better factors influencing participation in physical education (PE) and the mechanisms involved. The adolescent years are characterised by increasing levels of body-related concerns. In PE, the body is judged for its physical abilities and subject to social comparisons and body judgements. Grounded in the Self-Determination Theory, this study aimed to explore whether body-related factors were associated with adolescents’ involvement in PE and whether types of motivation mediated this relationship. Methods The study involved 2,140 (54.5% girls) secondary students (15–16-year-olds) from Norway participating in the nationally representative “Health Behaviour in School-aged Children (HBSC) study: a WHO collaborative cross-national study.” Body-related factors included Body Mass Index (BMI), health complaints, body perception and dietary behaviours. Gender, age, and socioeconomic status (family affluence) were control variables. Motivation for PE was assessed with the Perceived Locus of Causality (PLOCQ) scale measuring three distinct factors: autonomous motivation, controlled motivation and amotivation. PE involvement was self-reported as weekly participation in PE classes and time spent in moderate-to-vigorous physical activity (MVPA) during PE. Results Gender (girl), family affluence, health complaints, not being on a diet but wanting to lose weight, and body perception (too fat) were negatively associated with weekly PE participation when adjusting for other variables. This association was largely explained by students’ autonomous motivation in the case of health complaints and partly in the case of dietary behaviour and body perception. Similar results were observed for MVPA during PE lessons. Additionally, gender was associated with MVPA through amotivation. Conclusion The study adds new knowledge to the understanding of the relationship between body-related factors and PE, supporting that autonomous motivation is a central mechanism and an avenue for further research. The results should be considered in planning high-quality PE classes and suggest that an autonomous supportive learning climate sensitive to body-related concerns should be a priority to increase adolescent involvement in PE.